2020
DOI: 10.3389/fimmu.2020.573562
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Organoid Technology in Precision Medicine in Inflammation: Are We There Yet?

Abstract: Individualised cellular models of disease are a key tool for precision medicine to recapitulate chronic inflammatory processes. Organoid models can be derived from induced pluripotent stem cells (iPSCs) or from primary stem cells ex vivo. These models have been emerging over the past decade and have been used to reconstruct the respective organ-specific physiology and pathology, at an unsurpassed depth. In cancer research, patient-derived cancer organoids opened new perspectives in predicting therapy response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Moreover, it has been shown that the use of antibiotics impacts cell transcriptional activity (42) and differentiation (43). These alterations impact cellular hierarchy within the organoids and affect stem cell viability and growth rate, whose functionality is at the basis of organoid generation (40,(44)(45)(46). Indeed, ChIP-seq analysis of H3K27ac identified approximately 10,000 sites that were enriched near genes involved in cell differentiation, tRNA modification, nuclease activity, and protein dephosphorylation, in cells treated with P/S (42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the use of antibiotics impacts cell transcriptional activity (42) and differentiation (43). These alterations impact cellular hierarchy within the organoids and affect stem cell viability and growth rate, whose functionality is at the basis of organoid generation (40,(44)(45)(46). Indeed, ChIP-seq analysis of H3K27ac identified approximately 10,000 sites that were enriched near genes involved in cell differentiation, tRNA modification, nuclease activity, and protein dephosphorylation, in cells treated with P/S (42).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, organoid models are considered to be the closest in vitro model to simulate the in vivo physiological and pathological characteristics of diseases. 92 At present, organoid models of the intestines, lung, liver and stomach have been widely applied in the study of inflammation. As previously reported, organoid models have been used to evaluate the protective effect of TCM on intestinal damage (Glycyrrhetinic acid from Glycyrrhiza uralensis Fisch.…”
Section: The Classical Experimental Model Of the Anti‐inflammatory Ef...mentioning
confidence: 99%
“…First, customization of organoids in a reproducible manner demands extreme precision in standardization even in the presence of engineered matrices, while it is almost impossible using poorly defined decellularized extracellular matrices. Achieving the reproducibility level fitful for clinical bio-translation of the organoids requires the mandatory following of good manufacturing practices like the other pharmaceutical products, stringent specification of the ingredient as well as critical quality attributes of the customized organoids, and strict adherence to the predefined bioprocessing methods, customization protocols, and ethical guidelines approved by any international regulatory authorities ( Kim et al, 2020 ; Tran et al, 2020 ). Even the methods for scalability should comply with the international standard.…”
Section: Challenges and Future Prospectmentioning
confidence: 99%
“…Third, complete differentiation and full maturation of the organoid under the in vitro system often remain beyond the scope ( Truskey, 2018 ; Xu et al, 2018a , b ). Inadequate supply of nutrients, growth factors, and bioactive molecules, poor gaseous exchange, and stagnation of the wastes often limit the differentiation and maturation process ( Tran et al, 2020 ). Customization of organoids along with vasculatures using microfluidics platform or 3D bioprinting method or co-customization with blood-vessel organoid or fused organoid provides the promising means to overcome the limitation ( Ao et al, 2020 ; Chen et al, 2020 ; Zhang et al, 2020 ; Daly et al, 2021 ).…”
Section: Challenges and Future Prospectmentioning
confidence: 99%
See 1 more Smart Citation